2004
DOI: 10.1002/acp.1078
|View full text |Cite
|
Sign up to set email alerts
|

Memory and suggestibility in older adults: live event participation and repeated interview

Abstract: One hundred and thirteen young (mean age: 20.2 years) and older adults (mean age: 76.4 years) participated in an event that entailed various relaxation techniques, such as a body massage and aromatherapy. On two separate occasions several weeks following participation, half of each group was given misleading information about certain aspects of the event, including suggestions that they had been massaged on parts of their body which had not been touched. Results showed that older adults were disproportionately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
3
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
1
24
3
3
Order By: Relevance
“…This is inconsistent with previous research which found that episodic memory accounts by older adults are often less accurate and complete than those by younger adults (List, 1986;Mueller-Johnson & Ceci, 2004). It could be argued that the underperformance of younger adults was due to motivational differences.…”
Section: Discussioncontrasting
confidence: 56%
“…This is inconsistent with previous research which found that episodic memory accounts by older adults are often less accurate and complete than those by younger adults (List, 1986;Mueller-Johnson & Ceci, 2004). It could be argued that the underperformance of younger adults was due to motivational differences.…”
Section: Discussioncontrasting
confidence: 56%
“…Here we believe that the exposure may have led to a correction of the stereotype in the other direction. Indeed, some research has shown that older adults can be more suggestible than younger adults, (Karpel, Hoyer, & Toglia, 2001;Mitchell, Johnson, & Mather, 2003;Mueller-Johnson & Ceci, 2004;Polczyk et al, 2004). Thus it is possible that in this study exposure to seniors may not have led to generally more positive attitudes towards older adults, but perhaps to less stereotypical attitudes towards the elderly, correcting both positive and negative stereotypes.…”
Section: Discussionmentioning
confidence: 60%
“…than do younger adults (e.g., Cohen & Faulkner, 1989;Loftus, Levidow, & Duensing, 1992;Mitchell, Johnson, & Mather, 2003;Mueller-Johnson & Ceci, 2004; for a review, see Bartlett & Memon, in press). However, as Jacoby and colleagues have noted, these age-related differences may simply reflect older adults' reduced memory for what was learned, just as the age-related vulnerability to retroactive and proactive interference has been greatly reduced when older and younger adults have been matched on degree of initial learning (Jacoby, Bishara, Hessels, & Toth, 2005).…”
mentioning
confidence: 99%